Incidence, Histological Types and Age at Presentation of Borderline and Malignant Ovarian Tumors at a Tertiary Institute in Nepal - Bista, K D B (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The objective of this study was to find the incidence, assess the age and stage of presentation of ovarian malignancy and correlate these features with the histological types. Methods: Retrospective analysis of ovarian tumor cases that underwent primary surgery at our institute between April 2009 - April 2012 was done. Age, histological type, stage of the disease features were analyzed. Statistical analysis was done by Chi square and T test. Results: Out of 451 ovarian tumor cases, 81 cases of borderline and malignant ovarian tumor were seen. Germ cell tumors were the most common type of ovarian tumors. The mean age of presentation of primary malignant tumors was 41.9 years. Serous adenocarcinoma was the most common ovarian cancer occurring in 22.2 % (n =67) cases. In women <40 years the likelihood of germ cell cancer was significantly more than non germ cell malignancies (p value <0.001). Epithelial ovarian malignancies were more likely to present at late stages than non-epithelail malignancies and this was found to be statistically significant with p value of 0.003. Increasing age was associated with increasing stage of cancer. Conclusions: Germ cell tumors were the most common ovarian tumors, but epithelial tumors were the most common malignant ovarian tumors. Increasing age was associated with increasing stage of disease. DOI: http://dx.doi.org/10.3126/njog.v9i2.11736